Determination of stomatic density, index, and area as exposition biomarkers of pollution in Deschampsia antárctica Desv. (Poaceae) - Dopchiz, Laura Patricia (2022)
Fil: Dopchiz, Laura Patricia. Instituto Antártico Argentino. Laboratorio de Ecofisiología y Ecotoxicología; Argentina